Chitosan/collagen composite films as wound dressings encapsulating allantoin and lidocaine hydrochloride - YAŞAYAN, GÖKÇEN (TAYLOR & FRANCIS AS, 2021)
Chitosan/collagen composite scaffolds encapsulating allantoin and lidocaine hydrochloride were formulated in various ratios and characterized in vitro for their applications in wound healing. After fabrication, scaffolds were characterized in terms of topographical properties, surface roughness, and swelling behavior, and then their stabilities were monitored by hydrolytic and enzymatic degradation studies. Following compatibility studies among the active ingredients, drugs were encapsulated within scaffolds, and encapsulation efficiency and drug release studies were carried. Finally, in vitro cell viability and scratch wound healing assays were carried to assess scaffolds as wound dressings. Results suggest that blending of polymers with drugs changed topographical properties and surface roughness prominently. It is found that the formulation with chitosan/collagen ratio of 70/30 is more resistant to both hydrolytic and enzymatic degradation routes due to having favored properties of both collagen and chitosan. In vitro drug release studies indicated rapid release of drugs, hence the scaffolds could be advantageous for patients that need an immediate anesthetic effect in wound healing therapy. The cell culture studies demonstrated that the chitosan/collagen composite scaffolds showed no toxicity, and cell migrations were increased depending on the collagen ratio in scaffolds. These results suggest that chitosan/collagen scaffolds combined with allantoin and lidocaine hydrochloride could be a promising candidate for wound healing applications.
Keywords: Allantoin; chitosan; collagen; lidocaine hydrochloride; wound dressing; IN-VITRO; COLLAGEN SCAFFOLDS; HYALURONIC-ACID; SCRATCH ASSAY; ALOE-VERA; CHITOSAN; COMPATIBILITY; HYDROGEL; MANAGEMENT; CELLULOSE